THE EFFECT OF INJURIES ON THE PSYCHOLOGY AND LIFE OF A HUMAN AND THE FEATURES OF FORMING A HEALTHY, BALANCED PERSONALITY ACCORDING TO THE MARILYN MURRAY METHOD - ІLCHENKO, Ruslan; ІЛЬЧЕНКО, Руслан (Видавничо-поліграфічний центр “Київський університет”, 2024)
Background. The article reveals the topical issues of the impact of adverse experiences on the human psyche (psychological trauma, all types of violence, emotional deprivation). Emphasis is placed on the tendencies towards abuse of psychoactive substances, various types of addictions, destructive and auto-aggressive behavior, and maladaptations. It is noted about the effectiveness of using the Murray Method in overcoming the consequences of all types of psychological injuries of any severity, which covers almost all aspects of working with a person: from his inner experiences to interaction with other people. The program of rehabilitation of persons according to the Murray method reveals the process of trauma, violence, contempt, as well as the protective mechanisms of a person on the distortion of a person's mental perception and emotional response, which affects the health and behavior of a person. The result of the application of the rehabilitation program based on the Murray method is "the development of a healthy balanced personality" through the conscious and complete explanation of the consequences of the pain experienced in childhood, and the acquisition of knowledge and the development of skills for healthy behavior patterns in the present and future.Methods. Theoretical and methodological analysis of primary sources. Results. According to the Murray method, five groups of dysfunctions are distinguished for a person who was forced to experience trauma and did not process it: addictions, codependency, the state of the victim, manifestations of narcissistic traits, active and passive aggression. It is they who are an obstacle on the way to a full-fledged life of persons affected by injuries, and the subject of work in the rehabilitation program. Marilyn Murray's psychotherapeutic method is aimed at the formation of a healthy, balanced personality by overcoming psychological trauma, violence and deprivation. One of the basic concepts of M. Murray's concept is the "Original feeling child", which has talents and gifts, intelligence, creative abilities, healthy sexuality, spirituality, it is characteristic for her to harmoniously feel and express all feelings. Under the influence of adverse external factors, such as contempt, illness, injury, insult, etc., the essential integrity of the " Original feeling child " is destroyed – the "Sobbing hurting child" appears. The painful experiences that the "Original feeling child" felt during the trauma created her "Pool of Pain", where helplessness, fear, loneliness, sadness, anger, resentment, etc. accumulate – precisely such feelings that a person is not trained to express during trauma. A "Controlling Child" is added to protect the "Sobbing hurting child". A person becomes dependent on what helps them to avoid experiencing pain (drugs, food, alcohol, gambling, nicotine, sex, caffeine, work, constant employment, codependency, etc.). A harmonious combination of the strengths of the "Original feeling child", "Sobbing hurting child", and "Controlling Child" is a "Healthy balanced person".Сonclusions. M. Murray's therapeutic approach is based on sufficiently strong immersion in the "Pool of Pain" and its "devastation" in an atmosphere of support and love, reducing the role of the protective mechanism as a result of working with images, manifesting, talking about painful emotions, analyzing traumatic experiences, as well as searching and formation of personal talents, formation of a healthy, balanced personality, able to sympathize, show empathy, protect oneself without harming others, enjoy life.

Вступ. Розкрито актуальні питання впливу несприятливого досвіду на психіку і життя людини (психологічних травм, усіх видів насильства, емоційної депривації). Метою дослідження є опис особливостей формування здорової врівноваженої особистості за методом Мерилін Мюррей, розкриття основних понять методу.Методи. У дослідженні застосовано теоретико-методологічний аналіз першоджерел.Результати. Зазначено ефективність використання методу Мюррей у подоланні наслідків усіх видів психологічних травм будь-якого рівня тяжкості, який охоплює майже всебічно роботу з особистістю: від її внутрішніх переживань до взаємодії з іншими людьми.Висновки. Терапевтичний підхід методу Мюррей базується на достатньо сильному зануренні в атмосферу підтримки та любові, зниженні ролі захисного механізму в результаті роботи з образами, прояву, розмови про хворобливі емоції, аналізу травматичного досвіду, а також пошуку та формування особистісних талантів, формування здорової, врівноваженої особистості, здатної співчувати, виявляти емпатію, захищати себе, не завдаючи шкоди іншим, радіти життю.
ВПЛИВ ТРАВМ НА ПСИХІКУ І ЖИТТЯ ЛЮДИНИ ТА ОСОБЛИВОСТІ СТАНОВЛЕННЯ ЗДОРОВОЇ ВРІВНОВАЖЕНОЇ ОСОБИСТОСТІ ЗА МЕТОДОМ МЕРИЛІН МЮРРЕЙ
Keywords: Вперта егоїстична дитина; Дитина; яка плаче; Здорова врівноважена особистість; Контролююча дитина; Море болю; Природна дитина; Розгнівана бунтівна дитина»; Яйце травми